Hubungan Antara Pengetahuan, Sikap, Komitmen, Manajemen Laktasi, Dan Status Pekerjaan Dalam Pemberian ASI Eksklusif Pada Bayi Usia 0-24 Bulan Di Wilayah Puskesmas Kutabumi Pasar Kemis Kabupaten Tangerang Banten : Relationship Between Knowledge, Attitude, Commitment, Lactation Management, and Employment Status in Providing Exclusive Breastfeeding to Babies Aged 0-24 Months in the Kutabumi Public Health Center Area Pasar Kemis, Tangerang Banten Regency - Sari, Suci Novita; Nelasari (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Breast milk is a liquid that contains water, nutrients, living cells, and other components that are beneficial for the growth and development of babies. Exclusive breastfeeding is giving only breast milk without additional drinks or other fluids (such as formula milk, orange juice, honey, tea water, water, sugar water) and without additional food such as fruit, porridge, biscuits, or rice. Methods: This research design uses quantitative research with a cross-sectional design. The sample in this study was 109 respondents with a sampling technique using random sampling. The research instrument is a questionnaire. Researchers used the Chi-Square test. Results: By statistical test. It is known that there is no relationship between knowledge and exclusive breastfeeding for infants aged 0-24 months at Pasar Kemis Public Health Center in Tangerang Regency, Banten in 2022 with a p-value = 0,726. It is known that there is no relationship between attitude and exclusive breastfeeding for infants aged 0-24 months at Pasar Kemis Public Health Center in Tangerang Regency, Banten in 2022 with a p-value = 0,279. It is known that there is no relationship between commitment and exclusive breastfeeding for infants aged 0-24 months at Pasar Kemis Public Health Center in Tangerang Regency Banten in 2022 with a p-value = 0,553. It is known that there is no relationship between lactation management and exclusive breastfeeding for infants aged 0-24 months at Pasar Kemis Public Health Center in Tangerang Regency Banten in 2022 with a p-value = 0,479. It is known that there is a relationship between employment status and exclusive breastfeeding for infants aged 0-24 months at Pasar Kemis Public Health Center in Tangerang Regency Banten in 2022 with a p-value = 0,011 OR = 0,338. Discussion: There is no relationship between knowledge, attitudes, commitment, and lactation management with exclusive breastfeeding, but there is a relationship between employment status and exclusive breastfeeding at the Pasar Kemis Health Center.